First report of Pyricularia oryzae the cause of blast disease in upland rice, in Lombok, West Nusa Tenggara - IRNA IL SANURIZA; DEWA NGURAH SUPRAPTA; RETNO KAWURI; NI LUH SURIANI; I MADE SUDANTHA; IRFAN JAYADI; KHAERUL IHWAN (Biodiversitas Journal of Biological Diversity, 2024)
Rice (Oryza sativa L.) is a maincrop cultivated by farmers in Indonesia. The demand for rice has increased, but rice production has decreased due to attacks by plant pests, including pathogen blast disease. This research aims to (i) determine the symptoms of blast disease in upland rice in Lombok, (ii) determine the incidence of blast disease in upland rice in Lombok, (iii) and identify the pathogen that causes blast disease in upland rice in Lombok. The research was conducted in Lombok, West Nusa Tenggara. A sampling of rice crop tissue infected by blast disease was taken from 50  dryland locations in Lombok West Nusa Tenggara. From each point, three samples of rice crops with blast symptoms were taken to obtain 150 samples. Samples are then isolated and identified at the macroscopic, microscopic, and molecular levels. The study results showed that the macroscopic characteristics of rice leaves were rhombus-shaped and brown, and the pathogen produced white mycelium with a fine structure. In contrast, microscopic characteristics showed that the shape of the hyphae was septate, the structure of conidiophore with autophagic cell death, long pyriform microconidia, and long pyriform macroconidia. Based on 18S rRNA gene analysis, the Blast Lombok isolate had a DNA fragment of ±550bp. Based on these results, it can be concluded that the cause of blast disease in upland rice in Lombok, West Nusa Tenggara, is P. oryzae.